Coronary embolism due to possible thrombosis of prosthetic aortic valve - the role of optical coherence tomography: case report. Issue 7 (30th July 2021) - Kavaliauskaite, Raminta; Otsuka, Tatsuhiko; Ueki, Yasushi; Räber, Lorenz
Abstract: Background: Coronary embolism is an important non-atherosclerotic cause of acute myocardial infarction (AMI) that requires an individualized diagnostic and therapeutic approach. Although certain angiographic criteria exist that render an embolic origin likely, uncertainty remains. Optical coherence tomography (OCT) is a high-resolution intracoronary imaging technology that enables visualization of thrombus and the underlying coronary vessel wall, which may be helpful to distinguish between an atherosclerotic and non-atherosclerotic origin of AMI. Case summary : A 50-year-old male was admitted with ongoing chest pain. Eleven years ago, he underwent implantation of a mechanical aortic valve prosthesis due to degenerated bicuspid valve with normal coronaries on preoperative angiography. The electrocardiogram showed anterior ST-segment elevation. Emergent angiography revealed total occlusion of the proximal left anterior descending artery (LAD). Thrombus was aspirated along with administration of intravenous glycoprotein IIbIIIa inhibitor. Except the apical part of the LAD showing distal embolization, coronary flow was completely re-established with no evidence of significant atherosclerosis. Stents were not implanted on the basis of the OCT finding, which demonstrated at the site of occlusion a normal vessel wall without atherosclerosis that could explain an erosion or plaque rupture event. Transoesophageal echocardiography confirmed a floating structure in the left ventricular outflow tract, suggesting that an embolus originating from the prosthetic aortic valve obstructed the LAD. The international normalized ratio 2 days prior to presentation measured 1.9. Discussion : This case illustrates the utility of OCT to rule out the atherosclerotic aetiology of myocardial infarction and to avoid unnecessary stenting.